The Americas. - Academy of American Franciscan History (Washington, D.C. Academy of American Franciscan History, 1944)
"A quarterly review of inter-American cultural history."
Keywords: America -- History -- Periodicals; Latin America -- History -- Periodicals; United States -- Relations -- Latin America -- Periodicals; Latin America -- Relations -- United States -- Periodicals